Pengaruh Return On Asset (ROA), Debt To Asset Ratio (DAR), Dan Earning Per Share (EPS) Terhadap Harga Saham PT Mayora Indah Tbk - Yuniawati , Yuni; Istichanah, Istichanah; Agustiani, Rizki Muti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The aim of this research is to analyze the influence of Return On Assets (ROA), Debt To Asset Ratio (DAR), and Earning Per Share (EPS) partially and simultaneously on the share price of PT Mayora Indah Tbk for the 2015-2022 period. This research method uses secondary data taken through the official website of the Indonesia Stock Exchange regarding the financial reports and share prices of PT Mayora Tbk for the 2015-2022 period. With descriptive statistical analysis tools, classic assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination test (RðŸ). Based on the analysis, it was concluded that partial Return On Assets (ROA) did not have a significant effect on the share price of PT Mayora Tbk for the 2015-2022 period. Debt To Asset Ratio (DAR) partially has no significant effect on the share price of PT Mayora Tbk for the 2015-2022 period. Earnings Per Share (EPS) partially has a significant effect on the share price of PT Mayora Tbk for the 2015-2022 period. Return On Assets (ROA), Debt To Asset Ratio (DAR), and Earning Per Share (EPS) simultaneously do not have a significant effect on the share price of PT Mayora Tbk for the 2015-2022 period. Keywords: Return On Assets (ROA), Debt To Asset Ratio (DAR), Earning Per Share (EPS), and Share Price.